Reversible thermally induced spin crossover in the myoglobin-nitrito adduct directly monitored by resonance Raman spectroscopy - Valianti, Vasiliki K; Tselios, Charalampos; Pinakoulaki, Eftychia (My University, 2023)
Myoglobin has been demonstrated to function as a nitrite reductase to produce nitric oxide during hypoxia. One of the most intriguing aspects of the myoglobin/nitrite interactions revealed so far is the unusual O-binding mode of nitrite to the ferric heme iron, although conflicting data have been reported for the electronic structure of this complex also raising the possibility of linkage isomerism. In this work, we applied resonance Raman spectroscopy in a temperature-dependent approach to investigate the binding of nitrite to ferric myoglobin and the properties of the formed adduct from ambient to low temperatures (293 K to 153 K). At ambient temperature the high spin state of the ferric heme Fe-O-N[double bond, length as m-dash]O species is present and upon decreasing the temperature the low spin state is populated, demonstrating that a thermally-induced spin crossover phenomenon takes place analogous to what has been observed in many transition metal complexes. The observed spin crossover is fully reversible and is not due to linkage isomerism, since the O-binding mode is retained upon the spin transition. The role of the heme pocket environment in controlling the nitrite binding mode and spin transition is discussed.
Keywords: Binding energy; Electronic structure; Isomers; Metal complexes; Porphyrins; Raman spectroscopy; Spin dynamics; Stereochemistry; Transition metal compounds; Transition metals